2021
DOI: 10.15420/ver.2020.16
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel- and Sirolimus-coated Balloons in Peripheral Artery Disease Treatment: Current Perspectives and Concerns

Abstract: Drug-coated balloons (DCBs) have become an established therapy for the treatment of above-the-knee peripheral artery disease. The paclitaxel DCB has shown clinical benefit in terms of patency and freedom from re-intervention in multiple randomised trials. However, a recent meta-analysis has suggested an association between mortality and the use of paclitaxel-coated devices. Sirolimus is another potential choice of anti-proliferative agent for use in DCBs because of its wider therapeutic index and lower risk fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…14 While the efficacy of sirolimus over paclitaxel is still subject to investigation, with only limited pilot studies published on DCBs in the peripheral vasculature, 31 it has been suggested that it has a preferential therapeutic safety margin compared to paclitaxel and it has become the preferred drug coating for devices used in coronary artery intervention. 31 37 This could be setting a precedent for what is to occur in the peripheral vascular field. If sirolimus is to become the preferred drug-coating for DCBs used in peripheral vascular disease, investigation into its combined use with other techniques and devices is just as critical.…”
Section: Discussionmentioning
confidence: 99%
“…14 While the efficacy of sirolimus over paclitaxel is still subject to investigation, with only limited pilot studies published on DCBs in the peripheral vasculature, 31 it has been suggested that it has a preferential therapeutic safety margin compared to paclitaxel and it has become the preferred drug coating for devices used in coronary artery intervention. 31 37 This could be setting a precedent for what is to occur in the peripheral vascular field. If sirolimus is to become the preferred drug-coating for DCBs used in peripheral vascular disease, investigation into its combined use with other techniques and devices is just as critical.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these agents are both nonspecific and cytotoxic, and significantly increase the risk of long-term morbidity and mortality due to their off-target effects, which are activity that differs from the targeted biological effect [ 32 34 ]. Due to the broader therapeutic index and lower risk of dose-related toxicity, less mortality outcomes are expected for sirolimus [ 35 ]. On the other hand, a meta-analysis study comparing paclitaxel-coated devices with control arms showed that the mortality rate gradually increased in patients treated with paclitaxel-coated devices at follow-up up to the 5th year, despite a similar mortality rate at first year [ 36 ].…”
Section: Antiproliferative Effects Of Current Deb/des Usementioning
confidence: 99%